1995
DOI: 10.1164/ajrccm.151.1.7812537
|View full text |Cite
|
Sign up to set email alerts
|

Patient-ventilator interaction during synchronized intermittent mandatory ventilation. Effects of flow triggering.

Abstract: Synchronized intermittent mandatory ventilation (SIMV) intermixes assisted and spontaneous breaths. Its ability as a weaning technique has been questioned on the basis that patients show little adaptation to ventilator assistance. We studied inspiratory effort and patient-ventilator interaction at different levels (SIMV, 100, 50, and 0%) of flow-triggered SIMV versus pressure-triggered SIMV in patients during the weaning period. The two triggering systems were evaluated during constant flow and constant pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The degree of downregulation should depend on the sensitivity to CO 2 and the magnitude of PCO 2 reduction. Notwithstanding that the response to unloading might be related, to some extent, to baseline mechanical load or to the mode of mechanical ventilation [37], these results emphasize the importance of chemical feedback during mechanical ventilation. Paradoxically, the role of chemical feedback has been largely ignored by studies dealing with the effect of mechanical ventilation on respiratory muscle activity.…”
Section: Chemical Feedbackmentioning
confidence: 81%
See 2 more Smart Citations
“…The degree of downregulation should depend on the sensitivity to CO 2 and the magnitude of PCO 2 reduction. Notwithstanding that the response to unloading might be related, to some extent, to baseline mechanical load or to the mode of mechanical ventilation [37], these results emphasize the importance of chemical feedback during mechanical ventilation. Paradoxically, the role of chemical feedback has been largely ignored by studies dealing with the effect of mechanical ventilation on respiratory muscle activity.…”
Section: Chemical Feedbackmentioning
confidence: 81%
“…Chemical feedback could be a critical factor for this breath programming. These results have recently been challenged by GIULIANI et al [37], who showed that the mode of mechanical ventilation is important to show an effect of unloading on respiratory effort. They demonstrated that inspiratory effort was smaller in mandatory breaths than in spontaneous only if SIMV is applied with flow-triggering and constant pressure.…”
Section: Chemical Feedbackmentioning
confidence: 97%
See 1 more Smart Citation
“…Some ventilators have a fixed trigger, whereas in others the sensitivity can be varied. In the past, ventilators were usually pressure triggered, but it has been shown that flow-triggered devices are more sensitive than pressure-triggered devices [9][10][11]. The sensitivity of the inspiratory trigger needs to balance two extremes: 1) an insensitive trigger increases work of breathing; and 2) a trigger that is too sensitive leads to auto triggering.…”
Section: Pressure-targeted Ventilationmentioning
confidence: 99%
“…These "flow-by" or flow-triggered mechanisms have been compared to conventional demand-valve systems, and recent studies [58][59][60] have reported that flow-by systems, used either in CPAP or SIMV, are able to produce a significant decrease in respiratory work and other indices of inspiratory muscle effort when compared to the conventional demand-valve.…”
Section: Spontaneous Breathing With T-tubementioning
confidence: 99%